Implementasi Metode Regresi Linear Dalam Prediksi Harga Cabai Keriting Di Kota Samarinda - Lidya Sari; Novia Hidayati Ramadhani; Reyka Luna Karalo; Wawan Joko Pranoto (STIKes Ibnu Sina Ajibarang, 2024)
Chili is a popular vegetable in Indonesia, often used as a spice in various local dishes. The surge in demand before major celebrations, coupled with unpredictable weather, can impact chili production and lead to price fluctuations. Predicting prices becomes crucial to anticipate market changes and maintain economic stability in Indonesia. This study aims to predict the prices of curly red chili in Samarinda City in 2024 using the Linear Regression method. The data, sourced from the last three years (January 2021 to November 2023) via Lamin Etam's website, underwent processing with RapidMiner. Analysis using Root Mean Squared Error (RMSE) indicates an accuracy level of 240.487+/-, signifying a relatively large margin of error. These results underscore the importance of adding data attributes to enhance the accuracy of curly red chili price predictions in Samarinda City.